Metode Pengajaran dalam Al-Qur’an (Analisis QS. Al-‘An’am ayat 72 QS. al-Ra'd ayat 2) - Alfiyah, Avif (Program Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah dam Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2024)
The teaching methods in the Qur'an reflect deep and holistic educational principles, whichfocus not only on the transfer of knowledge, but also on the formation of character,spirituality and morality. In the Qur'an, teaching is carried out through various approaches,including the use of parables (mathal), stories (qishash), and direct dialogue between Allahand His people, which aim to convey divine messages effectively. This method emphasizes theimportance of reflection, deep understanding, and application of values in everyday life. Apartfrom that, the Qur'an also teaches methods of asking, speaking and listening attentively aspart of the learning process. Thus, the teaching methods in the Qur'an are not only orientedtowards intellectual knowledge, but also towards individual spiritual and moral development,which is in accordance with the demands of the times and the needs of humanity in seekingtruth and guidance in life. This research uses a qualitative approach by applying the Muqaran(comparative) interpretation method, which is a comparative interpretation approach usingthe interpretation of verses of the Koran written by mufassir to obtain a comprehensiveunderstanding of the interpretation of the theaching methods in al-Qur'an. The aim of thisresearch is to find out about the teaching methods in the Koran, especially in surah al-An'amverse 72 and surah al-Ra'd verse 2. Surah Al-An'am verse 72 contains various teachingmethods that can be applied in everyday life. This verse emphasizes spiritual education byteaching the basics of worship (prayer) and morality (piety) which are the foundation of aMuslim's life. This teaching method also teaches the importance of direct commands thatencourage changes in behavior, awareness of the final goal (hereafter), as well as theconnection between deeds and final results which people should always remember. Theteaching in this verse is practical, requiring people to carry out the teachings with fullawareness and sincere intentions. Surah Ar-Ra'd verse 2 describes a very in-depth teachingmethod, which involves teaching through natural phenomena, logical and clear explanations,deep reflection and understanding, and awareness of the ultimate goal of life. This teachingmethod teaches people to observe the universe and reflect on the greatness of Allah throughnatural phenomena, as well as connecting worldly life with the life of the afterlife. Theteaching in this verse aims to strengthen the people's faith and belief in meeting Allah in theafterlife and being responsible for every good deed